PELATIHAN DAN PENDAMPINGAN PERANCANGAN MEDIA INFORMASI DAN KONSELING KESEHATAN PADA REMAJA - Wibowo, Marsiana; Gustina, Erni; Mudayana, Ahmad Ahid (P3M STIKES Aisyiyah Surakarta, 2019)
Adolescents are time of great curiosity and experimentation and complex problems such as misbehavior, premarital sex, early marriage. It is important to describe to adolescent correct information and become supporter for her peoples especially in health promotion field. Teenagers are very adaptable to various changes and are very critical in responding to various information. Internet-based media is very popular among teenagers. However, the basics of designing and composing messages of these media are still low among teenagers. The purpose of this activity is to increase the knowledge and skills of adolescents in the design of information media and health counseling in Yogyakarta City. This workshop used skill development method with the activity of lecturing and practice which last for 2 days. The result of the workshop are to increase the knowledge of adolescent about information media and health counseling, to produce a product that is in the form of poster, and by utilizing Google Plus application, formed a forum with the name of Media Information and Counseling of Adolescent. Through this forum, teenagers can share information in various ways such as uploading media, sharing information links, and discussing about adolescents issues